The Impact of Artificial Intelligence Technologies on International Relations - A. D. Korobkov (Vestnik MGIMO-Universiteta)
The automation of human activity has been growing every year for the past ten years thanks to AI algorithms, increasing the amount of big data and computing power. Today, artificial intelligence technologies are used in everyday life, automating processes previously performed by humans. Moreover, it is believed that these technologies can reach human cognitive abilities and even surpass them at some point. In this regard, questions arise what the future of humanity will look like in conjunction with AI technologies. If earlier, most of the research was more technical, then in the last three to four years, there has been much scientific research in terms of disciplines in which the influence of artificial intelligence is possible. International relations are no exception. The purpose of the article is to review publications on how artificial intelligence technologies affect international relations? Within the framework of the article, six books and eight articles were considered. The author concludes that AI technologies seriously impact international relations in socio-economic and political terms. The socio-economic aspect includes the consequences of automated capitalism on world politics, the rise in unemployment, the emergence of a "hopeless" class, the polarization of society, and more. AI technologies influences strategic stability, nuclear deterrence, and cyber warfare.